Pengaruh Volume Penyiraman Air Terhadap Pertumbuhan Selada (Lactuca sativa L.) - Adika Muhammad Aziz; Ane Rizka Fauziyah; Azzahra Nabila Dwi Khairunnisa; Nadhira Nur Hukma; Rahmah Nurul Aina Hasanah; Taufik Rahman; Tri Suwandi (PT ADRIANI MANDIRI PUBLISHER, 2026)
Watering is an important activity as a plant growth process in order to survive. Determination of plant water needs is important to do, because plant water needs are the main limiting factor for plant productivity. Plant water needs can be determined based on the value of water content in the field capacity of the growing media. The aim of this study was to examine the effect of different volumes of watering on increasing growth and production of lettuce (Lactuca sativa L.). The study was carried out for 7 days with 3 treatments of watering volume, with each treatment carried out 6 times. The treatment tested was giving a different volume of water to each lettuce plant with three levels. Observations in this study were leaf cross-sectional area, number of leaves, and plant fresh weight. Experimental research with a qualitative descriptive approach and statistical data processing with the Kruskal Wallis Test. The results of data analysis showed that there was a relationship between the size of the volume of water in watering and the growth of lettuce plants